The employment consequences of anti-dumping tariffs: Lessons from Brazil - Gustavo De Souza; Haishi Li (Federal Reserve Bank of Chicago, 2022)
Can anti-dumping tariffs increase employment? We compile data on all antidumping (AD) investigations in Brazil matching it to firm-level administrative employment information. Using difference-in-differences, we find that, an AD tariff decreases imports and increases employment in the protected sector. Moreover, downstream firms decrease employment, while upstream ones are not affected. To quantify the aggregate effect of these tariffs, we build a model with international trade, input-output linkages, and labor force participation. We show that the Brazilian AD policy increased employment by 0.06%, but they decreased welfare by 2.4%. Using tariffs, the government can increase employment by as much as 2.8%.
Keywords: F13; F16; 330; employment; tariffs; anti-dumping; international trade